Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.7150/jca.29536
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-let-7e-5p Inhibits the Proliferation and Metastasis of Head and Neck Squamous Cell Carcinoma Cells by Targeting Chemokine Receptor 7

Abstract: This study aimed at determining the role of hsa-let-7e-5p in the progression of head and neck squamous cell carcinoma (HNSCC). The relative levels of hsa-let-7e-5p transcripts in 15 paired of HNSCC and adjacent non-tumor tissues and cells were examined by quantitative real-time PCR (qRT-PCR). The potential targets of hsa-let-7e-5p were predicted and validated by luciferase assay. The impact of altered hsa-let-7e-5p expression on HNSCC cell proliferation and metastasis was determined by CCK-8, wound healing, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…According to GLOBOCAN 2012, the age-standardized incidence of HNSCC in China is estimated to be 2.7 per 100,000 people 5. Despite advances in diagnosis and treatment, the 5-year survival rate of patients with HNSCC remains poor due to its high propensity for local and distant metastasis 6. The initiation and progression of HNSCC are linked to multiple risk factors including HPV, diet, detrimental habits, genetic background and geographic factors;7 however, the underlying molecular mechanisms are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…According to GLOBOCAN 2012, the age-standardized incidence of HNSCC in China is estimated to be 2.7 per 100,000 people 5. Despite advances in diagnosis and treatment, the 5-year survival rate of patients with HNSCC remains poor due to its high propensity for local and distant metastasis 6. The initiation and progression of HNSCC are linked to multiple risk factors including HPV, diet, detrimental habits, genetic background and geographic factors;7 however, the underlying molecular mechanisms are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…32 In addition, let-7e-5p overexpression inhibited cell proliferation, wound healing, migration, and invasion in head and neck squamous cell carcinoma cells. 33 Chiam et al found that circulating serum exosomal let-7e-5p may be a useful marker to distinguish esophageal adenocarcinoma from controls and Barrett's esophagus. 34 We supposed that circMYC may play a role in the function of downstream target genes by sponging miR-20b-5p and let-7e-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study also reveals that miR‐20b‐5p is sponged by circRNA DNA Methyltransferase 3 Beta (DMNT3B) in human retinal microvascular endothelial cell 32 . In addition, let‐7e‐5p overexpression inhibited cell proliferation, wound healing, migration, and invasion in head and neck squamous cell carcinoma cells 33 . Chiam et al found that circulating serum exosomal let‐7e‐5p may be a useful marker to distinguish esophageal adenocarcinoma from controls and Barrett's esophagus 34 .…”
Section: Discussionmentioning
confidence: 99%
“…reported that CCR7 could also be involved in the proliferation of head and neck squamous cell carcinoma [25]. Besides, Liu et al showed that CCR7 could promote dendritic cell migration by increasing glycolysis metabolism, and there was a negative feedback regulation [26].…”
Section: Tsccmentioning
confidence: 99%